The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12224-010-9096-z
|View full text |Cite|
|
Sign up to set email alerts
|

Impacts of Land Abandonment on Vegetation: Successional Pathways in European Habitats

Abstract: Changes in traditional agricultural systems in Europe in recent decades have led to widespread abandonment and colonization of various habitats by shrubs and trees. We combined several vegetation databases to test whether patterns of changes in plant diversity after land abandonment in different habitats followed similar pathways. The impacts of land abandonment and subsequent woody colonization on vegetation composition and plant traits were studied in five semi-natural open habitats and two arable habitats i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
63
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(75 citation statements)
references
References 60 publications
(60 reference statements)
6
63
1
3
Order By: Relevance
“…Hitherto, this scenario has been repeatedly observed over a wide range of habitats [13]. Nowadays, Molinietum caeruleae meadows [14] are among the world's most threatened habitats; their combined area has diminished gradually over recent decades throughout Europe [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, this scenario has been repeatedly observed over a wide range of habitats [13]. Nowadays, Molinietum caeruleae meadows [14] are among the world's most threatened habitats; their combined area has diminished gradually over recent decades throughout Europe [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly in plant ecology, numerous studies showed successional changes in species richness as well as community composition (e.g. Grime, 1979;Debussche et al, 1996;Prévosto et al, 2011;Knapp et al, 2016). At the beginning of a succession, the most important process structuring communities is the arrival of propagules from outside as well as the germination from the soil seed bank.…”
Section: Introductionmentioning
confidence: 99%
“…Smith and Smith, 2012), although patterns might be more complex (e.g. Prévosto et al, 2011). However, by restricting the measurement of biodiversity to species richness, one ignores almost 90 % of the "overall diversity" (Lyashevska and Farnsworth, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The landscape of Alps is considered one of the most important natural territories of Europe and provides a great number of ecosystem services (ESs): protection from natural hazards, CO2 storage and accumulation in soil or biomass, provisioning of raw materials and water, genetic diversity and touristic opportunities (Grêt-Regamey et al, 2008). During the second half of 20th century, socio-economic changes caused a modification in the use of Alpine territories towards a greater exploitation or a complete abandonment (Chauchard et al, 2007;Rutherford et al, 2008;Prévosto et al, 2011;Cocca et al, 2012). 876 FEDRIGOTTI et al These alterations are considered the main causes of variations observed in species diversity, ecosystem functionality, landscape configuration, and economical growth of the local communities (Tasser et al, 2005;.…”
Section: Introductionmentioning
confidence: 99%